ENPP1, an Old Enzyme with New Functions, and Small Molecule Inhibitors—A STING in the Tale of ENPP1 - Kenneth I. Onyedibe; Modi Wang; Herman O. Sintim (Molecules, 2019)
Ectonucleotide pyrophosphatase/phosphodiesterase I (ENPP1) was identified several decades ago as a type II transmembrane glycoprotein with nucleotide pyrophosphatase and phosphodiesterase enzymatic activities, critical for purinergic signaling. Recently, ENPP1 has emerged as a critical phosphodiesterase that degrades the stimulator of interferon genes (STING) ligand, cyclic GMP−AMP (cGAMP). cGAMP or analogs thereof have emerged as potent immunostimulatory agents, which have potential applications in immunotherapy. This emerging role of ENPP1 has placed this “old” enzyme at the frontier of immunotherapy. This review highlights the roles played by ENPP1, the mechanism of cGAMP hydrolysis by ENPP1, and small molecule inhibitors of ENPP1 with potential applications in diverse disease states, including cancer.